Fees, fairness and the National Scholarship Programme: Higher education policy in England and the Coalition Government (UCL Press, 2015)
Conservative and Liberal Democrat policies for higher education funding in the 2010 general election campaign offered voters a stark choice - with one party willing to consider raising the cap on undergraduate fees, while the other publicly committed to removing any student contribution. It is not surprising therefore that this was an area in which they found it impossible to agree a firm position as part of their coalition agreement (Cabinet Office, 2010). When parliament later voted on higher education funding, the view of the larger party prevailed and the cap on fees almost trebled to £9,000. The Liberal Democrat Deputy Prime Minister took responsibility for launching a National Scholarship Programme (NSP), providing financial support to undergraduates from lower-income backgrounds, to be introduced at the same time as the increase in fees. While this may have offered limited political credibility to his party, the structure of the scheme was criticized from the outset, and it ceased to operate after just three cohorts of students. This paper identifies the political and policy drivers behind the NSP. It explores the need for compromise in the context of the Coalition Government and the drive to embed a dimension of 'fairness' into policy change. From an analysis of the NSP's implementation, evolution, and ultimate closure, we consider the extent to which fairness can, and cannot, successfully be promoted through the design of undergraduate fees and financial support, an objective that was espoused by politicians responsible for the introduction of £1,000, £3,000 and, ultimately, £9,000 fees.